A Precise Definition of the Term “Corporate Social Costs”: An Initiative to Enrich the Thought of Accounting for CSR - Younis A. Battal Saleh (JAF (Journal of Accounting and Finance), 2025)
Purpose: This study aims to develop a precise definition of the term "corporate social costs (CSCs) "- according to accountants' point of view, and identify a set of criteria through which the corporate social cost (CSC) can be distinguished from the corporate economic cost (CEC). Method: Any theoretical study that aims to improve and develop the theoretical structure of any major in the social sciences such as economics and accounting often relies on the approach of rational thinking and logical inference. Hence, the researcher adopted this approach in studying and analyzing the nature of the costs incurred by companies to fulfill the requirements of legal and ethical responsibilities - which reflect the codified and uncodified desires of the stakeholders concerned with these responsibilities, as well as the nature of the benefits that these costs bring to the beneficiaries. The researcher also adopted the idea of the characteristics that can be deduced from these costs and the activities attributed to them in determining the criteria for distinguishing between CSCs and CECs. Results: Through logical conclusions, this study developed a precise definition of the term corporate social costs (CSCs), which is consistent with the contemporary concept of corporate social responsibility (CSR), and defined a set of criteria to distinguish CSCs from CECs. Originality /Value: Given the scarcity of writings in this field, this study is considered an enrichment of accounting thought in the field of CSR. This study will enhance the ability of companies to disclose their social performance accurately. On the educational level, this study will remove any misunderstanding students may have about the meaning of CSCs.